Validity and reliability of Malay version financial well-being scale among Malaysian employees - Mohammad Rahim Kamaluddin,; Rohany Nasir,; Wan Shahrazad Wan Sulaiman,; Sarah Waheeda Muhammad Hafidz,; Janetter Marcial@Nur Atiqah Abdullah,; Rozainee Khairudin,; Zainah Ahmad Zamani, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Financial well-being is perceived as one of the important parameters in measuring a person’s socio-economic status as well as his or her financial situation. While many measures are developed in the West to assess the financial well-being of an individual, a valid and reliable Malay translated scale is still lacking to measure Malaysians’ status of financial well-being. With that in mind, this study aimed to validate Financial Well-being Scale in Malay language (henceforth, FWS-M) among a sample of adult Malaysian employees. The present study commenced with Forward-Backward translations and subsequently subjected to various validation phases: face, content and construct validity. A total of 600 Malaysian employees aged 20 years and above were recruited for the purpose of construct and factorial validations using a random sampling method. The data was analysed using Exploratory Factor Analysis while Cronbach’s Alpha method was employed to identify internal consistency of the scale. The inter-item correlation between items were also ascertained using a Pearson Correlation Coefficient method. The results showed FWS-M is a unidimensional scale with the factor loading ranged between 0.62 and 0.88. Meanwhile, the reliability analysis of this scale revealed a Cronbach’s Alpha coefficient of 0.92, indicating promising internal consistency of the items. The inter-item correlation among items in FWS-M ranged between 0.37 and 0.79. FWS-M is concluded as a valid and reliable unidimensional instrument to assess financial well-being among Malaysians employees.